Nieznany znany poeta. O żydowskim aspekcie życia i twórczości Samuela Marszaka - Rzeszewska, Dorota (Studia Rossica Posnaniensia, 2012)
Samuil Marshak, the father of Soviet children’s literature, started his literary career as a supporter of Zionism, a movement that was particularly popular in the Russian Empire in the first decade of the 20th century. During the Stalinist era this descendant of great rabbinic families and author of the collections of poems Zionides and Palestine was forced to hide his Jewish roots. However, Jewish themes are present in Marshak’s pre-revolutionary and post-revolutionary work.